Distribution of suspended sediment based on tidal activity at Kuala Pidie, Sigli City. (December 2018) - Alhadi; Muhammad; Setiawan, I; Yuni, S M; Purnawan, S; Affan, J M; Ilhamsyah, Y; Wafdan, R
Abstract: Erosion and river flow affect the increase of suspended sediment loads. Sedimentation is the common problem found around the estuary. The purpose of this study is to determine the effect of tides during the new moon, full moon, ¼ half moon, and ¾ half moon to the concentration of suspended sediment around the waters of Kuala Pidie Sigli City. The station is determined using purposive sampling technique at 5 station and direct sampling technique is done by using 330 ml sample bottle. Sampling was taken during high tide for each condition of the lunar cycle, then analyzed in the laboratory. The results showed that the highest concentration was 7535 mg / L at station 1 when the low tide condition of the lunar month ¾, and the smallest was 100 mg / L at station 1 when the low tide condition of the new moon. The concentration of suspended sediments is affected by erosion and tidal currents. During full moon conditions, the concentration of suspended sediments at station 5 (downstream) is greater than station 1 (upstream).